Moral awareness among the perpetrators of incest crimes - Mohsen Obaid, Hijran; Daghestani, Sana Essa (Al-Adab Journal, 2021)
The current research deals with the study variable moral awareness (Moral awareness), which means the individual's knowledge of the impact of his potential actions and their limits on the ethical position by building possible perceptions of causes and consequences. In ethics, which is based mainly on understanding the three aspects of morality and unifying them (knowledge, sentiment and behavior) in one framework through which the interaction of the cognitive and emotional sides is clear.To achieve the objectives of the current research, the researcher relied on the theory of Rast (1986) and its four dimensions, which are moral sensitivity, moral judgment, ethical motivation, and ethical implementation. The two methods (the two extremes and internal consistency) and the validity of the construct was extracted using the Pearson correlation coefficient, and the stability coefficient of moral awareness by the Cronbach Alpha method reached (0,80), and the current research sample consisted of (250) prisoners of the Iraqi Ministry of Justice, and they were all male only, i.e. the Qaem Indeed, they are distributed among eight prisons of the Ministry of Justice, chosen randomly, and the research reached the following results: 1. Prisoners have an ethical awareness of statistical significance 2. There are differences in moral awareness according to the age variable, as for the achievement, the result indicates that there are statistically significant differences for the variable of moral awareness in favor of the university level and there are no statistically significant differences depending on the economic level.